Yellow fever: an emerging threat for Kenya and other east African countries. - Sanders, E; Tukei, P (1996)
Yellow fever (YF) is a well known disease that had plagued the tropics relentlessly until an effective vaccine was developed. Although the yellow fever vaccine is relatively affordable and one dose protects for over ten years, its use has predominantly been for known endemic areas of the world and international travellers. Eastern and southern African states, have hitherto been free of epidemic yellow fever, hence routine YF vaccination is not a policy in these countries. The sudden emergence of YF in the Rift Valley in Kenya in 1992-1993, introduces new dimensions into the challenges of YF to eastern and southern African states. Isolation of a virus deemed to be native of the area is discussed in this article in the context of YF policy issues confronting the region. A case has been argued for the establishment of a network of active surveillance systems in the region backed by adequate laboratory YF expertise locally, regionally, and internationally.